NOTA SÃ”BRE A OCORRÃŠNCIA DE Fusarium SP. CAUSANDO RESINOSE EM ABACAXÃ - Kimati, Hiroshi; Tokeshi, Hasime (REVISTA DE AGRICULTURA, 2016)
NOTA SÃ”BRE A OCORRÃŠNCIA DE Fusarium SP. CAUSANDO RESINOSE EM ABACAXÃ